Session-rpe is a valuable internal load evaluation method in beach volleyball for both genders, elite and amateur players, conditioning and technical sessions, but limited for tactical training and games: Session-RPE in beach volleyball (Kinesiology, 2020)
This study aimed to verify the validity of session-RPE method to monitor the internal training load (ITL)in beach volleyball players by considering sessions related to different genders, competition levels (elite oramateur), and types of session (conditioning, technical, or tactical/game). Session-RPE and Edwards’ methodswere applied to quantify the ITLs of 12 elite (18 players; 197 individual sessions) and 12 amateur (18 players;189 individual sessions) training sessions. Very large relationships between the two methods emerged forboth competition level (Elite: r=.77; Amateur: r=.75) and gender (male: r=.76; female: r=.75) subgroups, andconditioning sessions (r=.75). Large relationships emerged for technical (r=.61) sessions, whereas tactical/game sessions resulted only in moderate relationships (r=.36). Beach volleyball coaches could adequatelyuse session-RPE method to monitor training for players of different genders, competition levels, and typesof session, although tactical/game sessions should be considered with some caution.